HYBRID ENERGY STORAGE SYSTEM (HESS) DALAM SISTEM MINI-GRID TERPENCIL: TINJAUAN LITERATUR TERBARU - Defi, Sry; Fatana, Ahmad; Fathur Rachim, La Ode Muhamad; Larobu, Feliks Eldad (Jurnal Multidisipliner Kapalamada, 2025)
Hybrid Energy Storage Systems (HESS) have emerged as a promising solution to address reliability and stability challenges in remote mini-grid systems. This study presents a comprehensive literature review on the application of HESS in remote mini-grids, based on recent publications from 2020 to 2024. Through a systematic analysis of 45 scientific articles, this research identifies technological trends, implementation challenges, and future development opportunities for HESS. The findings reveal that the combination of lithium-ion batteries with supercapacitors and flywheels is the most popular configuration, achieving system efficiency improvements of up to 92% and operational cost reductions of 35%. The main challenges identified include the complexity of energy management systems, component sizing optimization, and high initial investment costs.